Local government performance: financial condition perspective - Sri Rahayu; Yudi Yudi; Rahayu Rahayu (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
The government performance measurement is essential to assess target achievement and public services, one of which is measured from the perspective of financial conditions. This study aimed to measure the performance of the regency and municipal in Jambi Province. The measurement used eight ratios of the basic factors of local governments' finance to analyze financial conditions. Furthermore, Jambi municipal and Sungai Penuh municipal are the regions with the best financial condition viewed from regional income factors. At the same time, Tanjabbar has the best financial condition from regional expenditure factors. From operational factors, the best position was held by three regions: Kerinci, Tanjabbar, and Sarolangun Regencies. Additionally, Muaro Jambi Regency has the best financial condition viewed from the debt structure factor. Overall, the regencies and municipalities in Jambi Province are in good financial condition. Four regions are averagely good, six regions have better financial conditions, and one region is in the best financial condition compared to those included in the assessment process.